2021
DOI: 10.1186/s40795-021-00426-2
|View full text |Cite
|
Sign up to set email alerts
|

Food and nutrition literacy status and its correlates in Iranian senior high-school students

Abstract: Background Planning interventions to promote food and nutrition literacy (FNL) require a better understanding of the FNL status of the target group and its correlates. Aims This study aimed to examine the FNL status and its determinants in Iranian senior high-school students. Methods In this cross-sectional study, FNL and its components (food and nutrition knowledge, functional skills, interactive skil… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
45
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(54 citation statements)
references
References 26 publications
(37 reference statements)
7
45
0
2
Order By: Relevance
“…This was further supported by other studies [29,30]. On the other hand, similar to our study in multiple regression models there was no significant association between BMI and nutrition literacy score [28]. Studies on the association between BMI and nutrition literacy are inconsistent [30,31] and may differ according to age and gender.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This was further supported by other studies [29,30]. On the other hand, similar to our study in multiple regression models there was no significant association between BMI and nutrition literacy score [28]. Studies on the association between BMI and nutrition literacy are inconsistent [30,31] and may differ according to age and gender.…”
Section: Discussionsupporting
confidence: 92%
“…Income was a significant predictor of nutrition literacy as well as living place which could reflect the importance of socioeconomic status on nutrition literacy. Similar to this study, a study among Iranian adolescents showed that mother education, higher socioeconomic status were associated with higher nutrition knowledge scores [28]. This was further supported by other studies [29,30].…”
Section: Discussionsupporting
confidence: 91%
“…Another study in urban Indonesia used maternal nutritional knowledge for obese mothers based on three dimensions such as macronutrients knowledge, household food measure skills, grouping food into categories skill and concluded that maternal knowledge has increased the self-efficacy in mothers and provided improvements in children growth behaviors ( 27 ). A study in Iran used food and nutrition knowledge assessment index using 60 items based on six dimensions such as knowledge on nutrition and food, functional skills, interactive skills, advocacy, critical investigation of information, and skills on reading a food label and concluded that nutrition knowledge level among senior-high-school students was low while academic performance and socioeconomic status were significant predictors ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…We developed the MNHA index based on previous studies (11)(12)(13)(14)(15)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40) searched from google scholar and Pubmed. We considered only those studies which tested the relationship between mothers' nutritional and health-related attitude/awareness and malnutrition.…”
Section: Development Of Health and Nutrition Awareness Indexmentioning
confidence: 99%
“…A handful of studies have been conducted on nutrition literacy among different subgroups of the population (i.e., adolescents, students, and adults) in Turkey ( 24 , 26 ), Taiwan ( 31 ), Iran ( 21 , 32 ), Palestine ( 28 ). However, there is a lack of available evidence investigating adults’ nutrition literacy, demographics, and personal beliefs in Bangladesh.…”
Section: Introductionmentioning
confidence: 99%